Physical exercise ameliorates age-related deterioration of skeletal muscle and mortality by activating Pten-related pathways in Drosophila on a high-salt diet. - Hou, W.Q.; Wen, D.T.; Zhong, Q.; Mo, L.; Wang, S.; Yin, X.Y.; Ma, X.F. (FASEB Journal (Federation of American Societies for Experimental Biology), 2023)
The phosphatase and tensin congeners (Pten) gene affects cell growth, cell proliferation, and rearrangement of connections, and it is closely related to cellular senescence, but it remains unclear the role of muscle-Pten gene in exercise against age-related deterioration in skeletal muscle and mortality induced by a high-salt diet (HSD). In here, overexpression and knockdown of muscle Pten gene were constructed by building Mhc[GAL4] /Pten[UAS-overexpression] and Mhc[GAL4] /Pten[UAS-RNAi] system in flies, and flies were given exercise training and a HSD for 2 weeks. The results showed that muscle Pten knockdown significantly reduced the climbing speed, climbing endurance, GPX activity, and the expression of Pten, Sirt1, PGC-1? genes, and it significantly increased the expression of Akt and ROS level, and impaired myofibril and mitochondria of aged skeletal muscle. Pten knockdown prevented exercise from countering the HSD-induced age-related deterioration of skeletal muscle. Pten overexpression has the opposite effect on skeletal muscle aging when compared to it knockdown, and it promoted exercise against HSD-induced age-related deterioration of skeletal muscle. Pten overexpression significantly increased lifespan, but its knockdown significantly decreased lifespan of flies. Thus, current results confirmed that differential expression of muscle Pten gene played an important role in regulating skeletal muscle aging and lifespan, and it also affected the adaptability of aging skeletal muscle to physical exercise since it determined the activity of muscle Pten/Akt pathway and Pten/Sirt1/PGC-1? pathway.